Adaptive fuzzy controller for controlling the dynamics of robot motion. (1st January 2014) - Sood, Vaishali; Kumar, Parveen
Autonomous robots are of prime importance in everyday life because of their capability to handle the non-linear situations. This paper describes the autonomous robot motion control system based on fuzzy logic proportional integral (PI) controller that reaches to its target value faster than others. Fuzzy rules are embedded in the controller to tune the gain parameters of PI controller and to move the robot along the task trajectory with variation in heading angle ( θ ) towards the target to make it helpful in real time applications. It discusses the design aspects of the fuzzy PI controller for controlling the dynamics of autonomous robot that have higher distribution rejection properties (DRP), low settling time (ST) and high adaptability towards the variation in the angle towards the target. The performance of a robot (RM) has been verified using MATLAB and results obtained have been found to be robust. Overall, the performances criteria in terms of its response towards ST, target acquisition (TA) and DRP have been found to be good.